Hybrid solid-porous titanium scaffolds: Fabrication and post processing after selective laser melting (Transactions on Additive Manufacturing Meets Medicine, 2019)
The aim of this study was to fabricate by selective laser melting hybrid solid-porous titanium scaffolds with regions of different porosities (500, 700 and 900 µm) controlled by the size of the diamond structure. In order to remove unmelted powder particles, obtain the required surface finish and render CAD model dimensions fabricated structures were chemically polished in a mixture of HF/HNO3 acids. The obtained results show that SLM combined with chemical post-processing is a perspective tool for fabrication of the hybrid titanium structures with properties which allows to mimics human bone to a greater extent than solutions utilized nowadays.